Lembar Kerja Peserta Didik dengan Pendekatan Pemecahan Masalah - Ravi, Ahmad; Ses Eka Polonia, Betti (Jurnal Inovasi Pendidikan Sains dan Terapan (INTERN ), 2024)
Problem-solving worksheets are educational resources that serve as a roadmap for instruction that give students methodical steps to hone their analytical, creative, and critical thinking abilities. This student problem-solving worksheet facilitates learning both individually and in groups by helping students comprehend the subject matter and practice skills. The purpose of this study is to evaluate the caliber of students' worksheets using a legitimate and useful technique to fluid material problem-solving. The four stages of a 4D research design—define, design, develop, and disseminate—are used in the process of product development. The study's findings demonstrate that employing a problem-solving strategy to validate students' worksheets produced a score for reliability of 1 with a suitable category. The proportion of responses from students